Psychometric Evidence of SRSS-IE Scores in Middle and High Schools. (December 2017) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Cantwell, Emily D.; Menzies, Holly Mariah; Schatschneider, Christopher; Lambert, Warren; Common, Eric Alan
We report results of an exploratory validation study of the Student Risk Screening Scale–Internalizing and Externalizing (SRSS-IE) applied with the first sample of middle and high school students from nine middle and three high schools from three states. The Student Risk Screening Scale (SRSS) was modified to broaden the scope of this user-friendly systematic screening tool to detect secondary-age students with internalizing behavior patterns. Building on initial evidence establishing reliability and validity of the SRSS-IE at the middle school level, we used classical test theory to explore reliability of SRSS-IE spring screening scores for use with sixth- through 12th-grade students. Specifically, we analyzed item-level data, internal consistency estimates, and factor structure using exploratory factor analysis. Results suggested five of the seven proposed items be retained, yielding the SRSS-IE12. Peer rejection (one of the originally developed items by Drummond) loaded on the internalizing construct, providing preliminary evidence suggesting two factors: SRSS-E7 (the original tool) and SRSS-I6 for use with secondary students, with peer rejection loading on both subscales but only added once when formulating the total score (SRSS-IE12). We present limitations and direction for future inquiry.